(untitled) (International Journal of Engineering and Computer Science, 2015)
Cloud computing is one of the latest computer and business industry buzz words. These days everyone wants to get rid of on desk burden. For example the Burden of on desk hardware (memory, hard disk, CPU), application software, system software, business continuity techniques, database ext. Cloud computing is one solution which provide all the above ‘As a service’. Cloud computing is a package of services. Data is no more Desktop bounded, you can access it from anywhere throughout world. Technological advancements – particularly the introduction of ‘cloud computing’ – have now made this a reality. This paper presents cloud as a service provider. Platform as a Service (PaaS) has become a bigger player in cloud computing, although it will continue to remain a smaller domain than Infrastructure as a Service (IaaS) and Software as a Service (SaaS). As the concept spread and offerings expanded, the industry has now embraced two flavors of cloud storage: public and private. Cloud computing is the way of doing business where the customer buys on demand, and the supplier charges for what the customer uses.. Due to Environmental benefits of cloud, it is on boom these days.